2008
DOI: 10.1016/j.scitotenv.2008.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of composts and liming materials in the phytostabilization of a mine soil using perennial ryegrass

Abstract: A microcosm experiment was carried out to evaluate the effects of municipal solid waste compost (MSWC) or garden waste compost (GWC), and liming materials in the rehabilitation of a soil affected by mining activities, and to study the use of perennial ryegrass (Lolium perenne L.) for phystostabilization. The performance of the amendments was assessed by soil chemical parameters, total and bioavailable metals (Cu, Pb and Zn), soil enzymatic activities, and plant relative growth and mineral composition. In gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(82 citation statements)
references
References 51 publications
6
71
0
Order By: Relevance
“…These are promising alternative technologies to traditional options of excavations and ex situ treatment, offering an advantage of being non-invasive and low cost. The purpose of revegetation is to stabilize the site, by providing a cover crop that will prevent dispersion of metalcontaminated particles by water and wind erosion and reduce metal mobility by rhizosphere-induced adsorption and precipitation processes (Alvarenga et al, 2008). However, plant growth is very limited in mine contaminated soils (high levels of metals and metalloids, soil acidity, low C and nutrients availability) and soil amendments such as lime, organic residues and industrial products such as zeolites and insoluble polyacrylate polymers promote the establishment of a vegetation cover by providing essential nutrients for plant growth, raising the pH, and chelating toxic metals (Alvarenga et al, 2008;2014;Guiwei et al, 2008;de Varennes et al, 2010;Pinto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are promising alternative technologies to traditional options of excavations and ex situ treatment, offering an advantage of being non-invasive and low cost. The purpose of revegetation is to stabilize the site, by providing a cover crop that will prevent dispersion of metalcontaminated particles by water and wind erosion and reduce metal mobility by rhizosphere-induced adsorption and precipitation processes (Alvarenga et al, 2008). However, plant growth is very limited in mine contaminated soils (high levels of metals and metalloids, soil acidity, low C and nutrients availability) and soil amendments such as lime, organic residues and industrial products such as zeolites and insoluble polyacrylate polymers promote the establishment of a vegetation cover by providing essential nutrients for plant growth, raising the pH, and chelating toxic metals (Alvarenga et al, 2008;2014;Guiwei et al, 2008;de Varennes et al, 2010;Pinto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies concerning the rehabilitation of polluted soils in situ have focused on the effects of different treatment on bioavailability of trace elements and plant growth (Alvarenga et al, 2008;Pérez-López et al, 2008), but interventions at one level inherently affect the restoration attributes at other levels (Kardold and Wardle, 2010). During decades, links between above-ground changes and belowground activities carried out by soil microorganisms were often ignored, although they are determinant of ecosystem resilience and functional efficiency, and they can assist restoration ecology (Kardold and Wardle, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…An analogical situation was observed when adding a mixture of compost from food waste and halloysite, although its influence was weaker. Alvarenga et al [65] found that the application of both composts and liming materials led to a decrease in the level of mobile/effectively bioavailable fractions of heavy metals.…”
Section: Effects Of Amendments On Soil Chemical Propertiesmentioning
confidence: 99%
“…However, procedures can be adapted to soils, using leachates extracted with water, in order to assess the impact of soil composition on ground water (Loureiro et al 2005;Alvarenga et al 2008a). Vibrio fischeri bioassays have demonstrated to be sensitive to heavy metals and can detect acute and sublethal effects caused by a large number of chemicals (Ribo and Kaiser, 1983).…”
mentioning
confidence: 99%
“…Chaîneau et al (2003) and Alvarenga et al (2008a) found that bioassays with V. fischeri and plant growth were very sensitive indicators, being more reliable to evaluate the reduction of adverse effects caused by toxicants than other bioassays, such as earthworm survival or seed germination. In the current study, although plant biomass was higher in 'Fe+PM' than in the 'NA' treatments, bioassays showed that this amendment addition does not create suitable conditions to the organisms assayed.…”
mentioning
confidence: 99%